Contemporary Arab-American literature : transnational reconfigurations of citizenship and belonging - Fadda-Conrey, Carol (London : NYU Press, 2014)
The last couple of decades have witnessed a flourishing of Arab-American literature across multiple genres. Yet, increased interest in this literature is ironically paralleled by a prevalent bias against Arabs and Muslims that portrays their long presence in the US as a recent and unwelcome phenomenon. Spanning the 1990s to the present, Carol Fadda-Conrey takes in the sweep of literary and cultural texts by Arab-American writers in order to understand the ways in which their depictions of Arab homelands, whether actual or imagined, play a crucial role in shaping cultural articulations of US ci.